A Qualitative Study of Factors That Influence Older Adults' Work on the Arduous Path to Spine Surgery - Andrea L. Strayer; Samantha Bjornson; Nicole E. Werner; Anna Krupp (Health Science Reports)
ABSTRACT Background and Aims Older adults worldwide are increasingly diagnosed with degenerative spine disease (DSD). Although older adults are frequently interacting with the healthcare system, clinicians are likely not aware of the many health‐related activities, or patient work that older adults engage in to achieve their health goals. An understanding of patient work is needed to guide patient‐oriented healthcare improvements for older people having surgery for DSD to achieve their desired health outcome. Our aim was to define factors in the patient work system that influence the patient work of older adults in the preoperative phase of spine surgery. Methods Secondary analysis of data (28 interviews) from older adults who underwent spine surgery, using deductive and inductive qualitative content analysis to describe patient work system factors. Components from the Systems Engineering Initiative for Patient Safety (SEIPS) 2.0 human factors ergonomics framework (person, organization, task, internal and external environments, tools/technology) guided 2‐member independent coding, codebook evolution, and team analysis. Results We identified 16 patient work system factors that influenced older adults' patient work during the preoperative time before spine surgery. The primary work system influencers included: severely limited physical function; inability to socialize; multiple providers and appointments; self‐management knowledge; emotions and mental state; active decision making; explaining treatment options; inability to complete household chores and self‐care; physical and emotional care and monitoring (by family); family coordinating care; household duties relinquished; complex scheduling of healthcare; home layout; insurance requirements; waiting for care; and devices to manage symptoms (medications; mobility hardware). Conclusions Factors that influence patient work are often a result of debilitating symptoms causing loss of independence, isolation, and confusion of how to meet their health goals. The influencing factors warrant research and process improvement initiatives. Thus, lessening the patient work burden and improving health outcomes.